The role of house prices in the monetary policy transmission mechanism in small open economies - Bjørnland, Hilde C.; Jacobsen, Dag Henning (Journal of Financial Stability, 2010)
We analyse the role of house prices in the monetary policy transmission mechanism in Norway, Sweden and the UK, using structural VARs. A solution is proposed to the endogeneity problem of identifying shocks to interest rates and house prices by using a combination of short-run and long-run (neutrality) restrictions. By allowing the interest rate and house prices to react simultaneously to news, we find the role of house prices in the monetary transmission mechanism to increase considerably. In particular, house prices react immediately and strongly to a monetary policy shock. Furthermore, the fall in house prices enhances the negative response in output and consumer price inflation that has traditionally been found in the conventional literature. Moreover, we find that the interest rate responds systematically to a change in house prices. However, the strength and timing of response varies between the countries, suggesting that housing may play a different role in the monetary policy setting.